Gold-catalyzed dual annulation of azide-tethered alkynes with nitriles: expeditious synthesis of oxazolo[4, 5-c]quinolines. Issue 14 (28th May 2019) - Su, Han; Bao, Ming; Pei, Chao; Hu, Wenhao; Qiu, Lihua; Xu, Xinfang
Abstract : A gold-catalyzed dual annulation of azide-tethered internal alkynes, which provides convenient access to quinoline derivatives, has been reported. Abstract : A gold-catalyzed dual annulation of azide-tethered internal alkynes with nitriles has been developed for the synthesis of oxazolo[4, 5- c ]quinolines in good to high yields under mild and neutral reaction conditions. Mechanistic studies indicate that this reaction is initiated by a gold-catalyzed 6- endo-dig azide-yne cyclization, followed by a [3 + 2] cycloaddition with external nitriles. In addition, the utility of the current method is illustrated by the synthesis of useful polyfunctionalized quinoline derivatives, including 3-aminoquinolin-4(1 H )-one and 3-hydroxyquinolin-4(1 H )-one.